Innate Antimicrobial Defense of Skin and Oral Mucosa - Philip W. Wertz; Sarah de Szalay (MDPI AG, 2020)
This special issue intends to review and update our understanding of the antimicrobial defense mechanisms of the skin and oral cavity. These two environments are quite different in terms of water, pH, and nutrient availability, but have some common antimicrobial factors. The skin surface supports the growth of a limited range of microorganisms but provides a hostile environment for others. The growth of most microorganisms is prevented or limited by the low pH, scarcity of some nutrients such as phosphorus and the presence of antimicrobial peptides, including defensins and cathelicidins, and antimicrobial lipids, including certain fatty acids and long-chain bases. On the other hand, the oral cavity is a warm, moist, nutrient rich environment which supports the growth of diverse microflora. Saliva coating the oral soft and hard surfaces determines which microorganisms can adhere to these surfaces. Some salivary proteins bind to bacteria and prevent their attachment to surfaces. Other salivary peptides, including defensins, cathelicidins, and histatins are antimicrobial. Antimicrobial salivary proteins include lysozyme, lactoferrin, and lactoperoxidase. There are also antimicrobial fatty acids derived from salivary triglycerides and long-chain bases derived from oral epithelial sphingolipids. The various antimicrobial factors determine the microbiomes of the skin surface and the oral cavity. Alterations of these factors can result in colonization by opportunistic pathogens, and this may lead to infection. Neutrophils and lymphocytes in the connective tissue of skin and mucosa also contribute to innate immunity.